Phát triển nghiên cứu liên ngành: Kinh nghiệm quốc tế và đề xuất chính sách cho các trường đại học Việt Nam - Nguyễn, Minh Hoàng; Nghiêm, Xuân Huy; Hoàng, Anh Tuấn (Tạp chí Giáo dục, 2025)
Interdisciplinary research (IDR) is increasingly recognized as vital for addressing complex societal issues. However, in Vietnamese universities, IDR development remains constrained by traditional governance structures, disciplinary silos, and fragmented support mechanisms. This study seeks to identify governance solutions that can promote IDR in Vietnam’s higher education institutions. Drawing on an analysis of current challenges and international practices, the paper proposes a set of integrated governance policies, including embedding IDR into institutional strategies, reforming organizational structures to reduce administrative barriers, enhancing leadership and coordination mechanisms, and adjusting evaluation systems to reflect the specific nature of IDR. These recommendations aim to support a more flexible, connected, and innovation-oriented model of university governance, better aligned with the demands of contemporary science and societal needs.